1999
DOI: 10.1136/gut.44.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Different intestinal permeability patterns in relatives and spouses of patients with Crohn’s disease: an inherited defect in mucosal defence?

Abstract: Background-A familial defect in intestinal barrier function has been found in Crohn's disease. Aim-To investigate possible genetic and environmental influences on this barrier defect by studying intestinal permeability in both relatives and spouses of patients with Crohn's disease. Subjects-The study included 39 patients with Crohn's disease, 34 healthy first degree relatives, and 22 spouses. Twenty nine healthy volunteers served as controls. Methods-Intestinal permeability was assessed as the lactulose:mannit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
150
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(160 citation statements)
references
References 36 publications
6
150
4
Order By: Relevance
“…Similar findings have been shown by Soderholm et al [23] . While Munkholm [32] and Jogerson et al [21] found a negative correlation of age with the absorption of mannitol and excretion of 51 CrEDTA, respectively.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Similar findings have been shown by Soderholm et al [23] . While Munkholm [32] and Jogerson et al [21] found a negative correlation of age with the absorption of mannitol and excretion of 51 CrEDTA, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…Jorgensen et al reported an association between the male gender and increased permeation of 14 C-mannitol [21] . On the contrary, Soderholm et al [23] did not find any correlation between IP and gender of the patients with CD. The reason of higher IP in male patients is not clear.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Currently, they are believed to be triggered and/or perpetuated by an increased leakiness of the epithelial barrier, disturbance of innate epithelial immune mechanisms, and disturbance of antigen recognition as well as processing of professional and atypical antigen-presenting cells [80][81][82]. Noteworthy, a disturbed regulatory and effector T cell balance appears also to be involved [83,84].…”
Section: Autoimmunity To Glycoprotein 2 In the Pathophysiology Of Cromentioning
confidence: 99%
“…While altered intestinal barrier function (increased intestinal epithelial permeability) can be a consequence of disease exacerbation, clinical evidence suggests it may also be a primary etiologic factor predisposing to disease development. For example, increased intestinal permeability is found not only in patients with IBD, celiac disease, and type I diabetes, but also their healthy first-degree relatives (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%